Exploring the formation of behavioral intention toward rural tourism via sensory experience and memorable tourism experiences, a case study in Henan, China - Zhenbin, Wang; Ramachandran, Sridar; Siow, Mayling; Subramaniam, Thanam; Hui, Zhang (Routledge, 2024)
This study aimed to investigate the formation of tourists’ behavioral intentions toward rural tourism by analyzing sensory experiences and memorable tourism experiences. The research was conducted through a case study in Henan, China. Using a quantitative approach, a survey was conducted where 490 participants completed a face-to-face questionnaire. The findings from the partial least squares structural equation modeling revealed that out of the five sensory experiences, only touch has a statistically significant and positive impact on behavioral intention. On the other hand, sight, sound, taste, and smell do not have a meaningful influence. In contrast, all five senses exhibited substantial beneficial effects on memorable tourism experiences. Memorable tourism experiences emerged to act as a mediator between the five senses and behavioral intention. This study is a pioneer attempt in the field of rural tourism, using the embodiment perspective to explore the mechanisms and connections linking sensory experiences, memorable tourism experiences, and behavioral intentions. The findings offer significant theoretical insights and practical contributions to advance the research and industry of rural tourism.